2018
DOI: 10.1088/1748-0221/13/03/c03039
|View full text |Cite
|
Sign up to set email alerts
|

Depleted fully monolithic CMOS pixel detectors using a column based readout architecture for the ATLAS Inner Tracker upgrade

Abstract: A: Depleted monolithic active pixel sensors (DMAPS), which exploit high voltage and/or high resistivity add-ons of modern CMOS technologies to achieve substantial depletion in the sensing volume, have proven to have high radiation tolerance towards the requirements of ATLAS in the high-luminosity LHC era. Depleted fully monolithic CMOS pixels with fast readout architectures are currently being developed as promising candidates for the outer pixel layers of the future ATLAS Inner Tracker, which will be installe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Moreover, previous e-TCT studies on test structures in LFoundry 150 nm CMOS [15] suggested that wafer thinning and back-side processing would result in an improvement in charge collection for irradiated thinned samples. By looking at their I-V curves (as depicted in Figure 3), the breakdown voltage was larger than 260 V independent of the sensor thickness or addition of metallization, in agreement with previous observations for unthinned samples [7,16]. I-V curves for back-side processed LF-Monopix samples of different thicknesses: 725 µm, 200 µm (with metallization) and 100 µm (without metallization).…”
Section: Leakage and Depletion After Thinningsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, previous e-TCT studies on test structures in LFoundry 150 nm CMOS [15] suggested that wafer thinning and back-side processing would result in an improvement in charge collection for irradiated thinned samples. By looking at their I-V curves (as depicted in Figure 3), the breakdown voltage was larger than 260 V independent of the sensor thickness or addition of metallization, in agreement with previous observations for unthinned samples [7,16]. I-V curves for back-side processed LF-Monopix samples of different thicknesses: 725 µm, 200 µm (with metallization) and 100 µm (without metallization).…”
Section: Leakage and Depletion After Thinningsupporting
confidence: 88%
“…TJ-Monopix is a DMAPS prototype with pixels using a small electrode for charge collection [7,8]. The chip was designed in a modified 180nm CMOS sensor process from Towerjazz, where a 1 kΩ cm epi-layer can be fully depleted through the addition of a low dose n-type implant [9].…”
Section: Tj-monopixmentioning
confidence: 99%
“…Moreover they must be able to comply with the 25ns timing requirement of the ATLAS experiment. DMAPS prototypes manufactured in different technologies have been reported with encouraging results regarding the sensor radiation tolerance [4,5,6,7]. Additionally, multiple nested wells offered by modern CMOS processes allow for complex readout circuitry to be implemented inside the pixel, enabling the use of fast readout architectures.…”
Section: Introductionmentioning
confidence: 99%
“…LF-Monopix is a depleted MAPS (DMAPS) prototype program [120,121,130] aiming for ATLAS. The concept of the sensor relies on sizeable 250 × 50 µm pixels with high fill factor diodes.…”
Section: Lf-monopixmentioning
confidence: 99%